Youth and the Rural Economy in Africa: Hard Work and Hazard 2021
DOI: 10.1079/9781789245011.0009
|View full text |Cite
|
Sign up to set email alerts
|

Young people's imagined futures.

Abstract: This chapter explores the futures that rural young people in Africa imagine for themselves, and how they relate to both their current engagement with the rural economy, and the narrative that suggests a widely held desire to abandon agriculture and rural areas. Beyond imagined future economic activities, including farm and non-farm work, the chapter highlights the place of education and migration in young people's imagined futures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…1: Two stylised local rural economies with which women can engage to build their livelihoods Source: Authors' construct Women's engagement in a closed rural economy is likely to be limited to domestic work, and on-farm family labour. Farming on their own accord is likely to be extremely challenging for women owing to difficulties in accessing productive resources including land (Boafo and Yeboah, 2022;AGRA, 2015;Yeboah and Flynn, 2021), although family and social relations, in addition to the rental land markets may provide a pathway for women to access land to start farming (Yeboah et al, 2020;Asciutti et al, 2016;Berckmoes and White, 2016;Bezu and Holden, 2014). In such an economy, the difficulties with accessing land for farming may compel women or (anyone else) to move to alternative spaces (rural or urban) in search for livelihood opportunities (Yeboah et al, 2021).…”
Section: A Local Economy Perspective To Women's Livelihood Building I...mentioning
confidence: 99%
See 1 more Smart Citation
“…1: Two stylised local rural economies with which women can engage to build their livelihoods Source: Authors' construct Women's engagement in a closed rural economy is likely to be limited to domestic work, and on-farm family labour. Farming on their own accord is likely to be extremely challenging for women owing to difficulties in accessing productive resources including land (Boafo and Yeboah, 2022;AGRA, 2015;Yeboah and Flynn, 2021), although family and social relations, in addition to the rental land markets may provide a pathway for women to access land to start farming (Yeboah et al, 2020;Asciutti et al, 2016;Berckmoes and White, 2016;Bezu and Holden, 2014). In such an economy, the difficulties with accessing land for farming may compel women or (anyone else) to move to alternative spaces (rural or urban) in search for livelihood opportunities (Yeboah et al, 2021).…”
Section: A Local Economy Perspective To Women's Livelihood Building I...mentioning
confidence: 99%
“…Farming on their own accord is likely to be extremely challenging for women owing to difficulties in accessing productive resources including land (Boafo and Yeboah, 2022;AGRA, 2015;Yeboah and Flynn, 2021), although family and social relations, in addition to the rental land markets may provide a pathway for women to access land to start farming (Yeboah et al, 2020;Asciutti et al, 2016;Berckmoes and White, 2016;Bezu and Holden, 2014). In such an economy, the difficulties with accessing land for farming may compel women or (anyone else) to move to alternative spaces (rural or urban) in search for livelihood opportunities (Yeboah et al, 2021). However, gender, cultural and social norms may shape women's ability to move to other places in search of such opportunities (Thorsen and Yeboah, 2021).…”
Section: A Local Economy Perspective To Women's Livelihood Building I...mentioning
confidence: 99%
“…poor skills development; lack of access to credit, broadband and extension services) for youth people interested in working the land for a living. Whilst the adoption of new agricultural technologies like improved irrigation schemes, satellites providing accurate climatic data and/or the use of smartphones and the Internet, is unquestionable (Yeboah & Flynn, 2021) in stimulating interest amongst youth, it is understanding their needs that is critical. Findings demonstrated that young people do not see value in completing Grade 12 (matric) if they are not able to use it for gainful employment or further education. Thus, national government efforts should include re‐aligning educational training with industry employment needs through engaging youth, teachers and local employers to ensure that the curriculum and delivery of these educational programs respond to labour market needs.…”
Section: Implication For Practicementioning
confidence: 99%